Development of cut chrysanthemum production in two soilless systems - Taweesak, Viyachai; Abdullah, Thohirah Lee; Hassan, Siti Aishah; Kamarulzaman, Nitty Hirawaty; Wan Yusof, Wan Abdullah (Elsevier, 2015)
Chrysanthemum is an important cut flower grown widely in Cameron Highland, Malaysia. The chrysanthemum growers encountered soil-born diseases, nematodes and accumulation of salinity when production in the same area was practiced continuously. Soilless culture was a cultivation technique independent from soil condition. The purpose of this research was to determine the growth of chrysanthemum grown in two soilless systems included tray system and trough system. The tray system used seedling trays (50 holes, 140 cm3/hole) as container, and the trays were arranged over the raise base covered with polyethylene sheet. Cuttings of chrysanthemum ‘New Yellow’ were grown in the tray and arranged at density 81 plants/m2. Each plant was irrigated by drip emitter 6 times/day with nutrient solution containing N 200, P 60, K 300 Mg 50, S 75, Fe 12, Mn 2, B 0.3, Cu 0.1, Zn 0.1 mg/L. The trough system was made from polyethylene sheet with a thickness of 0.04 mm laid over polyethylene sheet. The height of the trough was 15 cm and the width was 1 m. Chrysanthemum cuttings were grown in trough containing of coconut peat thickness 10 cm height and plants were fertigated with nutrient solution by drip tape once a day for three weeks, after that the plants were fertigated three times a week. The growth and flowering of chrysanthemum in the two systems were observed. The growth and quality of flowers produced in the tray and the trough system were similar. No significant differences in flower characteristics were observed between the two systems except for flower color. Chrysanthemum produced in both soilless systems received the same price for grade A as soil grown chrysanthemum. This indicated that chrysanthemum production in soilless system can be adopted to eliminate soil related diseases in the highlands.